Effect of Leadership on Organic Farming Adoption Decision - Rittinon, Chonnakan; Uruyos, Manachaya (Asian Journal of Applied Economics, 2017)
This paper studies the effects of leadership and neighborhood on organic farming adoption decision with Spatial Autoregressive Probit Model (SAR Probit). The observations of this study are 289 rice farmers in Chiang Rai, Payao, Nan, Suphanburi and Ayutthaya which includes 99 chemical farmers and 190 organic farmers. There are two main findings from this study. First, trustworthiness, age, farm ownership, sex, education and organic farming knowledge openness positively affects the decision in organic farming adoption. Second, SAR Probit model show that there is a spatial effect on organic farming adoption decision. In other words, Neighbors decision have important role in organic farming adoption decision of farmers. There are two policy suggestions. First, supporting organic farming knowledge through trustworthiness leader or organization. Second, initially supporting group of farmers with the tight relationship due to the exist of positive spatial effect and trustworthiness on organic farming adoption decision